Granulometria do calcário para podeiras comerciais submetidas ou não á iluminação artificial - Xavier, Regina Patrícia de Souza (2013)
The experiment was conducted to evaluate the effects of particle size of the limestone and the use of artificial light on feeding behavior, performance, egg quality and bone of laying hens. A total of 300 Hisex White hens at 18 weeks of age, distributed in a completely randomized design in factorial 5 x 2, with 5 replicates of 6 birds. The factors studied were 5 granulometries obtained by increasing the proportion of coarse limestone (0, 25, 50, 75 and 100%) compared to 2 types of thin and light, with and without artificial light. No significant interaction between factors (size x lighting program) for all parameters evaluated on performance, egg quality and bone. There was also no significant effect on the level of coarse limestone in diets on performance and egg quality, however had an effect on bone quality. Among the light programs, showed that the use of artificial light showed eggs with higher Haugh Units compared to birds that received only natural light. With respect to feeding behavior no significant interaction between factors limestone, light and time. However, significant effects of the interaction (light and time), there was a higher consumption in birds without artificial light in relation to artificial light during the hours of 6am to 9h40min and 12:40 to 17:40 and the interaction effect (limestone and time) , it was observed that at the time of 6am to 9h40min, increased consumption, corresponded to the gradual increase in the ration of coarse limestone. For laying hens in the first laying cycle, created in geographic coordinates that developed in the research, changes in particle size of limestone provided an improvement in bone quality of the birds and the use of artificial light may favor albumen quality as Haugh unit.